DAYA HAMBAT SARI BUAH BELIMBING WULUH (Averrhoa bilimbi, L) TERHADAP PERTUMBUHAN BAKTERI Eschericia coli. - Oktavianes, Oktavianes; Fifendy, Mades; Handayani, Dezi (Pendidikan Biologi, 2013)
ABSTRACTStarfruit ( Averrhoa bilimbi, L ) is a plant that most organs have high medical value, starting from the roots, stems, leaves to fruit. The fruits used as traditional medicine for cough, bleeding gums, canker sores, cavities pain, acne, tinea versicolor, high blood pressure, strokes, improve digestive function. Starfruit has active substances such as tannins, saponins, and flavonoids which can be used as an antimicrobial agent. Escherichia coli is a bacteria found in human colon as normal flora, but E. coli for many years regarded as a cause of diarrhea. Research has been conducted in order to determine the inhibition of starfruit juice ( Averrhoa bilimbi, L ) on the growth of E. coli. This research was conducted at the Laboratory of Biology X Kopertis of West Sumatra in May-June 2013. This research used Completely Randomized Design ( CRD ) with 6 treatments and 4 replications. Concentration of strat fruits juice was 10 %, 20 %, 30 %, 40 %, 50 %, and 10 % Amoxylin as control. The result showed that the largert diameter of clear zone present in a concentration of 10 % that is 3.74 mm, while the lowest diameter at a concentration of 30 % which is 3.29 mm and the control amoxilin gained an average of 4.13 mm. The results showed that the starfruit juice ( Averhoa bilimbi, L ) affected the growth of E. coli bacteria. At a concentration of 10 % with an average diameter of the clear zone is 3.74 mm was able to inhibit the growth of bacteria E. coliÂ